(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Digital transformation of spheres of human life involves the development and implementation of artificial intelligence technologies, particularly in the educational system. The article covers the potential of organising adaptive learning in the context of the war in Ukraine. It determines the theoretical foundation, defines the essence of artificial intelligence technologies, and presents their classification and areas of application. It determines the advantages of using artificial intelligence technologies in the organisation of the educational process of a higher education institution. The platforms and specialised software using artificial intelligence technologies that ensure the organisation of adaptive learning are characterised. It is noted that the most optimal platform for the use of artificial intelligence, particularly chat-bots, is Telegram, which creates not only a platform for communication and posting diverse information, but also serves as a means of organising an individual educational trajectory and allows one to upload files and exchange educational content. JavaScript language is used for implementing Telegram educational chat-bot’s multi-functionality. The article theoretically grounds and presents the algorithm for the application of artificial intelligence, in particular, a chat-bot, in the conditions in the context of adaptive learning in the pedagogical institution of higher education. It highlights the features of using chat bot for studying the discipline "Engineering and Computer Graphics". The chat-bot is implemented on the Node.JS platform, using the Node-Telegram-Bot-API library. The results of a pedagogical experiment are presented, which included a survey on the effectiveness of using artificial intelligence, in particular Telegram, to organize adaptive learning among students and teachers. The results of the survey among students showed that the use of telegrambot is appropriate in the process of professional training, as it provides quick access to various types of information through the integration of web applications, intelligent systems and access to intelligent artificial intelligence systems. Teachers noted that in the process of using telegrambots, direct contact with students decreased, they noted that the chatbot's reaction was not always correct, low Internet connection speed, insufficient digital skills of teachers to create adaptive digital environments, IT security problems, and uncertainty in using modern digital standards. A comparison of the survey data of students and teachers shows that telegrambots are in demand among students and require the development of digital skills of teachers in creating and implementing adaptive digital environments using artificial intelligence technologies.